2022
DOI: 10.1080/21655979.2022.2076453
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of icariin in a myocardial infarction mouse model

Abstract: Myocardial infarction (MI) is a prevalent cardiovascular disease defined by myocardial ischemia and hypoxic damage caused by plaque rupture, thrombosis, lumen stenosis, or blockage in the coronary artery. However, the development of emergency percutaneous coronary interventional therapy has enabled the rapid restoration of blood perfusion to ischemic myocardium and the rescue of dying myocardium cells. Some dying myocardium cells have caused irreversible damage and impaired cardiac function recovery in recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The neuroprotective characteristics of this phytochemical against Alzheimer's and Parkinson's diseases are mediated by affecting several biomolecules and molecular pathways such as amyloid precursor protein, β-site amyloid precursor protein cleaving enzyme 1 (BACE1), insulin-degrading enzyme, ERK1/2, GSK-3, NF-κB, Nrf2, and PI3K [80]. The inhibition of myocardial apoptosis, the prevention of inflammation on endothelial cells, the improvement of the immune system function, and the activation of HO1/ Nrf2 signaling pathways are reported as the modulatory mechanisms by which icariin exerts its therapeutical properties against cardiovascular disorders [85,86]. Furthermore, the antimicrobial function of this phytoestrogen, such as ameliorating Escherichia coli lipopolysaccharide-mediated endometritis, is suggested to be performed by inhibiting oxidative stress and inflamma GMJ.2022;11:e2809 www.gmj.ir tion [87].…”
Section: Icariin a Novel Phytochemical With Favored Medicament Proper...mentioning
confidence: 99%
“…The neuroprotective characteristics of this phytochemical against Alzheimer's and Parkinson's diseases are mediated by affecting several biomolecules and molecular pathways such as amyloid precursor protein, β-site amyloid precursor protein cleaving enzyme 1 (BACE1), insulin-degrading enzyme, ERK1/2, GSK-3, NF-κB, Nrf2, and PI3K [80]. The inhibition of myocardial apoptosis, the prevention of inflammation on endothelial cells, the improvement of the immune system function, and the activation of HO1/ Nrf2 signaling pathways are reported as the modulatory mechanisms by which icariin exerts its therapeutical properties against cardiovascular disorders [85,86]. Furthermore, the antimicrobial function of this phytoestrogen, such as ameliorating Escherichia coli lipopolysaccharide-mediated endometritis, is suggested to be performed by inhibiting oxidative stress and inflamma GMJ.2022;11:e2809 www.gmj.ir tion [87].…”
Section: Icariin a Novel Phytochemical With Favored Medicament Proper...mentioning
confidence: 99%
“…In an LAD-induced MI model, isoliquiritigenin (ISL) or icariin significantly reduced the myocardial infarction area, improved cardiac function, inhibited ROS and MDA production, suppressed SOD and GPx consumption through increased nuclear Nrf2 and cytosolic HO-1 levels and reduced OS after AMI (Sai et al, 2022;D. Yao et al, 2022).…”
Section: Flavonoidsmentioning
confidence: 99%
“…In an LAD-induced MI model, isoliquiritigenin (ISL) or icariin significantly reduced the myocardial infarction area, improved cardiac function, inhibited ROS and MDA production, suppressed SOD and GPx consumption through increased nuclear Nrf2 and cytosolic HO-1 levels and reduced OS after AMI ( Sai et al, 2022 ; D. Yao et al, 2022 ). Furthermore, in mice or rats with STZ-induced diabetes mellitus or high glucose-cultured H9c2, ISL attenuated inflammation and OS and protected against aortic injury through upregulation of Nrf2 and HO-1 (X.…”
Section: Protective Effects Of Natural Products On Cvdsmentioning
confidence: 99%
“…Subculture was carried out when the cells reached 80-90%. The logarithmic growth cells were divided into the following groups: (1) DMSO group, (2) ICA group (cells were treated with 30 μM ICA for 48 h 19 ), (3) ethanol group, (4) curcumol group (cells were treated with 211.55 μM curcumol for 48 h), (5) ICA + curcumol group (cells were treated with 30 μM ICA and 211.55 μM curcumol for 48 h), ( 6) ICA + curcumol +3-MA (cells were treated with 30 μM ICA, 211.55 μM curcumol and 10 mM 3-MA for 48 h 20 ), (7) ICA + curcumol + Fer-1 (cells were treated with 30 μM ICA and 211.55 μM curcumol and 2 μM Fer-1 for 48 h 21 ).…”
Section: Cell Culture and Groupingmentioning
confidence: 99%
“…Icariin (ICA), a flavonoid compound isolated from the TCM Epimedium, has a wide range of biological efficacy in bone porosity, cardiovascular diseases, and immune function regulation. 6,7 Curcumol is a sesquiterpene compound with pharmacological activities such as anti-tumor, antiviral, and anti-inflammatory. 8 Studies have shown that both ICA and curcumol have therapeutic effects on PCa.…”
Section: Introductionmentioning
confidence: 99%